Sex difference in frontal plane hip moment in response to lateral trunk obliquity during single-leg landing - Shohei Taniguchi; Tomoya Ishida; Masanori Yamanaka; Ryo Ueno; Ryohei Ikuta; Masato Chijimatsu; Mina Samukawa; Yuta Koshino; Satoshi Kasahara; Harukazu Tohyama (BMC, 2022)
Abstract Background Lateral trunk obliquity during landing is a characteristic of anterior cruciate ligament (ACL) injuries in female athletes and affects their knee and hip kinetics and kinematics. However, it is unclear whether these effects differ between females and males. The purpose of this study was to compare the effects of lateral trunk obliquity on knee and hip kinetics and kinematics in females and males during single-leg landing. Methods Eighteen female (aged 22.1 ± 1.5 years) and 18 male participants (aged 21.8 ± 1.1 years) performed single-leg landings under two conditions: (1) without any instructions about trunk position (natural) and (2) with leaning their trunks laterally 15° from the vertical line (trunk obliquity). The kinetics and kinematics of their hip and knee were analyzed using a three-dimensional motion analysis with a force plate. Two-way repeated-measures ANOVA (sex × trunk obliquity) and Bonferroni pairwise comparisons were conducted. Results The trunk obliquity angle at initial contact was significantly greater in the trunk-obliquity landing condition than in the natural landing condition (natural 4.0 ± 2.2°, trunk-obliquity 15.1 ± 3.6°, P < 0.001) with no sex difference (95% CI − 1.2 to 2.2°, P = 0.555). The peak knee abduction moment was significantly larger in the trunk-obliquity landing condition than in the natural landing condition (trunk-obliquity, 0.09 ± 0.07 Nm/kg/m; natural, 0.04 ± 0.06 Nm/kg/m; P < 0.001), though there was no sex or interaction effect. A significant interaction between sex and landing condition was found for the peak hip abduction moment (P = 0.021). Males showed a significantly larger peak hip abduction moment in the trunk-obliquity landing condition than in the natural landing condition (95% CI 0.05 to 0.13 Nm/kg/m, P < 0.001), while females showed no difference in the peak hip abduction moment between the two landing conditions (95% CI − 0.02 to 0.06 Nm/kg/m, P = 0.355). Conclusions The knee abduction moment increased with a laterally inclined trunk for both female and male participants, while the hip abduction moment increased in males but not in females. It may be beneficial for females to focus on frontal plane hip joint control under lateral trunk-obliquity conditions during single-leg landing.